The legal status of memoranda of understanding in relation to treaties for the avoidance of double taxation and information exchange - Masilo, Phuthehi (Department of Commercial Law, 2021)
It has been suggested by international lawyers that Memoranda of Understanding (MOUs) are instruments concluded between States which they do not intend to be governed by international law (or any other law) and, as a result, are not legally binding. The question as to what legal status MOUs have in the context of international tax law, particularly in relation to treaties for the avoidance of double taxation and information exchange has, to a greater extent, not been asked or answered in academic literature. This minor dissertation seeks to address that. Based on a review of the legal framework for treaties and MOUs, analyses of cases dealing with tax MOUs, and taking into consideration doctrinal work of various commentators, it is evident that the legal status of tax MOUs is determined by the role they play in the interpretation and application of tax treaties. The key finding arising from the research presented in this minor dissertation is that the roles of tax MOUs are to complete the treaty or modify or clarify substantive provisions of the treaties they are based on. If they complete or modify the treaty, such MOUs have legal consequences. On the other hand, if they only clarify substantive treaty provision, they do not have direct legal consequences but can be considered for interpretation purposes. Although MOUs have been viewed historically as non-legally binding agreements not governed by international law or any other law, evidence seem to suggest a contrary view in the context of international tax treaty law. If an MOU is concluded pursuant to a treaty article, through the powers given to Competent Authorities (CAs) under articles 25(1)-(3) of the OECD Model Tax Convention (MTC) to conclude, for example, an interpretive instrument, then arguably such an MOU is intended to be governed by international law as the treaty authorises its conclusion. MOUs of this kind concluded by CAs have binding effects.